PENGARUH PERBANDINGAN FASE GERAK PADA ANALISIS DEKSAMETASON MENGGUNAKAN HPLC : NARRATIVE REVIEW - Hening, Putik Titian Citra; Rahayu, Ihsanti Dwi; Iqbal, Muhammad; Triyandi, Ramadhan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Dexamethasone is a synthetic glucocorticoid widely used in the treatment of inflammatory, allergic, and autoimmune diseases; therefore, accurate analytical methods are required to ensure its quality and safety. High Performance Liquid Chromatography (HPLC) is an analytical technique that is currently widely applied due to its high sensitivity, selectivity, and reliability for pharmaceutical analysis. In HPLC method development, the selection of the mobile phase can significantly influence separation quality, resolution, column efficiency, retention time, sensitivity, and analytical reproducibility. Consequently, appropriate mobile phase selection is a major concern in achieving accurate, precise, and efficient analytical methods. However, to date, no review article has comprehensively compiled and discussed the effect of mobile phase variations specifically on dexamethasone analysis using HPLC. This review article aims to evaluate the effect of variations in mobile phase composition in HPLC analytical methods on the quality of dexamethasone analysis. A literature search was conducted using Google Scholar, PubMed, and Scopus databases, with inclusion criteria consisting of full-text articles published between 2015 and 2025 in Indonesian or English. Based on the selection and screening process, ten articles met the eligibility criteria and were included for further analysis. The results of this review indicate that mobile phase composition plays a crucial role in chromatographic separation performance and method validation parameters. Mobile phases containing a high proportion of organic solvents, particularly acetonitrile, tend to produce shorter retention times, improved peak symmetry, and sharper peak shapes. Meanwhile, the addition of buffer systems to the mobile phase improves pH stability, sensitivity, and linearity.